1999
DOI: 10.1006/viro.1999.9631
|View full text |Cite
|
Sign up to set email alerts
|

A GroEL Homologue from Endosymbiotic Bacteria of the WhiteflyBemisia tabaciIs Implicated in the Circulative Transmission of Tomato Yellow Leaf Curl Virus

Abstract: Evidence for the involvement of a Bemisia tabaci GroEL homologue in the transmission of tomato yellow leaf curl geminivirus (TYLCV) is presented. A approximately 63-kDa protein was identified in B. tabaci whole-body extracts using an antiserum raised against aphid Buchnera GroEL. The GroEL homologue was immunolocalized to a coccoid-shaped whitefly endosymbiont. The 30 N-terminal amino acids of the whitefly GroEL homologue showed 80% homology with that from different aphid species and GroEL from Escherichia col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
125
0
9

Year Published

2001
2001
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 205 publications
(138 citation statements)
references
References 39 publications
(51 reference statements)
4
125
0
9
Order By: Relevance
“…The virion is known to concentrate itself in the accessory salivary gland of the host until it is released into the phloem of a healthy plant during the next infestation cycle of the aphid (3,4,34) The symbionin has been found to have extensive sequence homology (varies from aphid to aphid in the range of 80 -92%) to the E. coli GroEL chaperonin. Both of them are also identical in terms of their quaternary association (35). A, shows the interaction of the two mannose residues with the ASAL amino acid residues.…”
Section: Identification Of the Bbmv Receptors By Ligand Bindingmentioning
confidence: 97%
“…The virion is known to concentrate itself in the accessory salivary gland of the host until it is released into the phloem of a healthy plant during the next infestation cycle of the aphid (3,4,34) The symbionin has been found to have extensive sequence homology (varies from aphid to aphid in the range of 80 -92%) to the E. coli GroEL chaperonin. Both of them are also identical in terms of their quaternary association (35). A, shows the interaction of the two mannose residues with the ASAL amino acid residues.…”
Section: Identification Of the Bbmv Receptors By Ligand Bindingmentioning
confidence: 97%
“…In aphids and whiteflies, GroEL homologues are circulating in the haemolymph outside the bacterial cells [58]. It has been shown that virions bind to these GroEL homologues, thereby escaping destruction by the vector's immune system and allowing virus transmission [58,59]. It is not always clear whether GroEL of facultative or primary symbionts is involved in this process, and therefore it is unknown how much variability there is within the vector species.…”
Section: Are Heritable Endosymbionts Affecting Important Ecological Tmentioning
confidence: 99%
“…The viruses have exploited the constitutive over expression of heat shock protein by the endosymbiotic bacteria in these insects by using GroEL as a receptor to anchor and enter the insect mid gut. Further, since GroEL of these endosymbionts is a secreted protein (while in normal free living bacteria, it is a cytoplasmic protein), the virus when bound to GroEL can easily be transported into the haemolymph up to the salivary gland [41,42]. Thus, the increased level of GroEL, necessary for proper functional activity of the endosymbiont's protein, is high jacked by the viruses to gain entry into the insect.…”
Section: Immunity and Protectionmentioning
confidence: 99%